IMPLEMENTASI SISTEM MANAJEMEN MERIT DALAM PENGEMBANGAN KARIR JABATAN PEMERINTAHAN DI KABUPATEN SINJAI - Ade Ardiansyah; Abdul Mahsyar; Fatmawati (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of the implementation of the merit system in the career development of State Civil Apparatus (ASN) in Sinjai Regency, identify structural and cultural barriers, and formulate strategic recommendations. Using a descriptive-interpretive qualitative approach, data were collected through semistructured interviews with echelon III-IV structural officials, participatory observation, and analysis of policy documents and performance reports. The results of the study show that the merit system in Sinjai has been implemented based on three pillars of qualifications, competence, and performance but is still partial. Only 2.3% of the 4,561 ASN (especially echelon II) have their competencies validated, while echelon IV and functional positions have not been touched by the assessment due to the absence of local assessment centers and the limited number of certified assessors. The main challenges include low budget allocation (5% for training), disparities in understanding of the merit system among employees, and lack of transparency in promotion decision-making. However, this system managed to reduce 40% of nepotism complaints (2021–2023) and increase the public health service satisfaction index by 15%. The discussion underlined the urgency of strengthening structural policies, such as the Sinjai Regent Regulation No. X/2023 for standardization of promotion criteria, collaboration with universities in the preparation of assessment instruments, and the use of realistic simulation-based assessment centers. Recommendations include budget increases, multilevel socialization, and the formation of an independent oversight team. These findings confirm that the success of the merit system at the district level requires integration between political leadership, supporting infrastructure, and merit-based work culture change. This research contributes to the literature on regional civil service governance by highlighting the unique dynamics of meritocracy implementation in the local context.